Use of prohibition order after a large outbreak of gastroenteritis caused by a norovirus among function attendees - Siranda Torvaldsen; Sophie Norton; Essi Huhtinen; Rowena Boyd; Rodney McCarthy; John Shields; Craig Shadbolt; Catriona Furlong; Kirsty Hope; Leena Jupta; Praveena Gunaratnam (World Health Organization Regional Office for the Western Pacific, 2012)
Introduction: In May 2011, an outbreak of acute gastroenteritis occurred among guests attending two functions (Function A and B) at a local function centre in Sydney, Australia. The Sydney South West Public Health Unit and the New South Wales (NSW) Food Authority sought to determine the cause of the outbreak and implement control measures.Methods: A retrospective cohort study was planned. A complete guest list was unavailable, so guests who could be contacted were asked to provide details of other guests. Attendee demographics, symptom profile and food histories were obtained using a standard response questionnaire. Stool samples were requested from symptomatic guests. The NSW Food Authority conducted a site inspection.Results: Of those interviewed, 73% of Function A guests and 62% of Function B guests were ill, with mean incubation times of 27 and 23 hours respectively. Diarrhoea was the most common symptom. Three stool samples and four environmental swabs were positive for norovirus. One food handler reported feeling ill before and during the functions. A prohibition order was used to stop food handlers implicated in the outbreak from preparing food.Discussion: This outbreak strongly suggests transmission of norovirus, possibly caused by an infected food handler. Regulatory measures such as prohibition orders can be effective in enforcing infection control standards and minimising ongoing public health risk.